The mediating effects of smartphone addiction in the association between mental disorders and eating disorders: findings from a nationwide survey among Chinese youth - Runping Ma; Kaiyuan Min; Ziyan Meng; Juntao Yang; Hui Zhang; Qing Li (BMC Public Health)
Abstract Background The prevalence of eating disorders among youth has increased in recent decades, with significant health consequences. Depression, loneliness and social anxiety are associated with eating disorders. However, the underlying mechanisms of these associations remain insufficiently explored. Considering the possibility that mental disorders increase the risk of smartphone addiction and that smartphone addiction is associated with eating disorder in adolescents, this study aims to investigate whether smartphone addiction mediates the association between mental disorders and eating disorders. Methods Between October and November 2023, we conducted an online survey among youth across 31 provincial-level administrative divisions (PLADs) in China. To align our sample composition with official statistics for each PLAD in terms of gender and school type, we applied sample weights to each respondent. Structural equation modeling (SEM) was used to examine the mediating effects. To assess the consistency of these results, we also performed analyses for each gender and age group. Results Among 10,000 weighted participants, 51.7% are male, with a median age of 16 years (IQR: 14–19). About 40% of youth experienced eating disorders. Smartphone addiction partially mediated the association between depression, loneliness, social anxiety, and eating disorders, contributing 24.69% (95% confidence interval: 20.60%-28.79%), 32.33% (95% CI: 27.53%-37.12%), and 37.35% (95% CI: 31.79%-42.91%) of the total effects, respectively. No heterogeneity was observed when analyses were stratified by gender and age group. Conclusion Smartphone addiction must be taken into account when designing strategies to prevent eating disorders in adolescents, which requires the cooperation of schools, parents and the government.